The effectiveness of ozone therapy in splinting teeth. - Ashrafov , Davud Sergey; Kerimova, Gulara Elhan; Aliyev , Mammad Suad Afrail (Actual Dentistry, 2024)
Abstract: The purpose of this work is to study the condition of periodontal tissues during splinting of teeth. During the period of immobilization, along with the main treatment, it is necessary to carry out a set of measures aimed at preventing the progression of inflammatory and destructive changes in periodontal tissues. To prevent complications, various general and local drugs are used, in particular antiseptics, antibiotics and sulfonamide drugs. In recent years, various methods of modern physiotherapy have become increasingly used to prevent complications in dentistry, which determined the main content of this study.